2021
DOI: 10.4314/sajas.v51i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour, welfare, and tibia traits of fast- and slow-growing chickens reared in intensive and free range systems

Abstract: The behaviour, welfare, and tibia characteristics of fast- and slow-growing chickens were evaluated in free-range and intensive production systems. A total of 720 birds of three strains were subjected to these systems after 21 days of rearing under the same intensive environment. Each treatment was replicated six times with 20 birds in each replicate. Data were collected for welfare aspects, including feather condition, footpad, hock joint and tonic immobility, behavioural features, especially feeding or forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, several studies concluded that genetic factors enabling a fast growth rate might negatively affect broiler health and behaviour and, thus, welfare 4 . For instance, studies performed under experimental conditions have reported that fast growth in broilers is a risk factor for high mortality 2,5 , poor adaptive immune system function 6 , increased prevalence of metabolic disorders 7 and skeletal disorders leading to gait abnormalities and lameness 8 , lower activity levels 5,9,10 , higher scores for foot pad lesions and hock burns 5,10 and poor feather condition 10 .Consumer concern for animal welfare has resulted in the development of a market segment using broilers with slower growth rates 11 . Indeed, an increasing proportion of slower growing broilers is used in European broiler production; e.g.…”
mentioning
confidence: 99%
“…However, several studies concluded that genetic factors enabling a fast growth rate might negatively affect broiler health and behaviour and, thus, welfare 4 . For instance, studies performed under experimental conditions have reported that fast growth in broilers is a risk factor for high mortality 2,5 , poor adaptive immune system function 6 , increased prevalence of metabolic disorders 7 and skeletal disorders leading to gait abnormalities and lameness 8 , lower activity levels 5,9,10 , higher scores for foot pad lesions and hock burns 5,10 and poor feather condition 10 .Consumer concern for animal welfare has resulted in the development of a market segment using broilers with slower growth rates 11 . Indeed, an increasing proportion of slower growing broilers is used in European broiler production; e.g.…”
mentioning
confidence: 99%
“…(2021) reported that 8-week-old FR broilers showed a much longer TI duration than indoor-raised chickens. On the other hand, according toGhayas et al (2021) andMutibvu et al (2017) fear response was less (TI duration was shorter) in FR group than intensive system. We can say that the ndings are contradictory again.…”
mentioning
confidence: 82%
“…Indeed, recent studies under experimental conditions indicated that genetic selection for fast growth is an important risk factor for mortality in broiler chickens ( Havenstein et al, 2003 ; Dixon, 2020 ). In addition, previous studies found associations between fast growth and adaptive immune system function ( Cheema et al, 2003 ), metabolic function ( Lubritz et al, 1995 ), lameness ( Kestin et al, 2001 ), and feather condition ( Ghayas et al, 2021 ). Studies comparing mortality between hybrids of different growth rates are scarce; however, 2 observational studies reported lower mortality during the first week and during the entire production period for slower growing broilers ( Rayner et al, 2020 ; Baxter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 94%